Response rate of initial conventional treatments, disease course, and related factors of patients with adult-onset Still's disease: Data from a large multicenter cohort. (May 2016) - Kalyoncu, Umut; Solmaz, Dilek; Emmungil, Hakan; Yazici, Ayten; Kasifoglu, Timucin; Kimyon, Gezmiş; Balkarli, Ayşe; Bes, Cemal; Ozmen, Mustafa; Alibaz-Oner, Fatma; Erten, Sükran; Cagatay, Yonca; et al.
Abstract: Background: Adult-onset Still's disease (AOSD) is a rare condition, and treatment choices are frequently dependent on expert opinions. The objectives of the present study were to assess treatment modalities, disease course, and the factors influencing the outcome of patients with AOSD. Methods: A multicenter study was used to reach sufficient patient numbers. The diagnosis of AOSD was based on the Yamaguchi criteria. The data collected included patient age, gender, age at the time of diagnosis, delay time for the diagnosis, typical AOSD rash, arthralgia, arthritis, myalgia, sore throat, lymphadenopathy, hepatomegaly, splenomegaly, pleuritis, pericarditis, and other rare findings. The laboratory findings of the patients were also recorded. The drugs initiated after the establishment of a diagnosis and the induction of remission with the first treatment was recorded. Disease patterns and related factors were also investigated. A multivariate analysis was performed to assess the factors related to remission. Results: The initial data of 356 patients (210 females; 59%) from 19 centers were evaluated. The median age at onset was 32 (16–88) years, and the median follow-up time was 22 months (0–180). Fever (95.8%), arthralgia (94.9%), typical AOSD rash (66.9%), arthritis (64.6%), sore throat (63.5%), and myalgia (52.8%) were the most frequent clinical features. It was found that 254 of the 306 patients (83.0%) displayed remission with the initial treatment, including corticosteroids plus methotrexate with or without other disease-modifying antirheumatic drugs. The multivariate analysis revealed that the male sex, delayed diagnosis of more than 6 months, failure to achieve remission with initial treatment, and arthritis involving wrist/elbow joints were related to the chronic disease course. Conclusion: Induction of remission with initial treatment was achieved in the majority of AOSD patients. Failure to achieve remission with initial treatment as well as a delayed diagnosis implicated a chronic disease course in AOSD. Highlights: Uncertainties in the diagnosis and treatment of adult onset Still's (AOSD) disease needs large comprehensive data. Induction of remission was mostly achieved with moderate/high doses of corticosteroids and methotrexate/hydroxychloroquine. Biological agents were needed in a small group of patients, and were effective in patients resistant to other drugs. Delayed diagnosis of more than 6 months and failure to remission with initial treatment related with chronic disease course.